APLIKASI PENCARIAN JUDUL TUGAS AKHIR MAHASISWA BERBASIS VISUAL STUDIO 2012 DAN MYSQL - Sri Tria Siska; Arif Budiman; Hilda Fenia (Rang Teknik Journal, 2023)
The application to search for student final assignment titles at the Payakumbuh College of Technology is still being done manually, namely written in a book that has been provided by the admin of the computer engineering study program, thus storing the data has not been computerized so that it can result in human error. Therefore, it is felt less effective and efficient. Because in searching for data for the title of the final assignment, you have to look at it one by one so that there are no similarities between other upper-level students, to do the search takes a relatively long time, the data stored in the book can also be lost by the computer engineering study program admin. So there is a need for an application to search for student final assignment titles at the Payakumbuh College of Technology using Visual Studio 2012 and MySQL. The existence of this search application makes it easier for the computer engineering study program admin to see lists of names of students who have taken the title of the final assignment. The admin of the computer engineering study program can make a search in a short time and doesn't take a long time. In addition, the admin of the computer engineering study program can also perform data archiving by inputting the data into this application, be it student data, lecturer data and title data so that it can overcome the loss of data. The data that has been input can also be printed according to annual data and individual data.